Assessment of lower urinary tract function in children with Down syndrome. Issue 6 (15th October 2014) - Kitamura, Atsuko; Kondoh, Tatsuro; Noguchi, Mitsuru; Hatada, Teppei; Tohbu, Shohei; Mori, Ken‐ichi; Matsuo, Manabu; Kunitsugu, Ichiro; Kanetake, Hiroshi; Moriuchi, Hiroyuki
Abstract: Background: Despite the fact that functional lower urinary tract symptoms are common among people with Down syndrome (DS), their voiding function has not been studied precisely. Our goal was to assess the lower urinary tract functions in DS. Methods: Fifty‐five DS children aged 5–15 years old and 35 age‐matched control children were evaluated by ultrasonography and uroflowmetry. Results: Eleven (20%) DS children had no uresiesthesia, 21 (38%) were urinated under guidance, nine (16%) urinated fewer than three times a day, two (4%) urinated more than 10 times a day, three (5%) used diapers, and 26 (47%) had urinary incontinence. Seven (13%), 15 (27%), and 10 (18%) DS children had weak, prolonged and intermittent urination, respectively, and seven (13%) had urination with straining. In contrast, none of the control subjects had urinary problems. In the uroflowmetrical analysis, 10 (18%), 20 (37%), 11 (20%) and five (9%) DS children showed "bell‐shaped, " "plateau, " "staccato" and "interrupted" patterns, respectively; the remaining nine (16%) could not be analyzed. In contrast, 21 (60%), one (3%), four (11%), three (9%) and two (6%) control subjects showed bell‐shaped, tower‐shaped, plateau, staccato and interrupted patterns, respectively; the remaining four (11%) could not be analyzed. Residual urine was demonstrated in four (7%) DS children and one (3%) control child. Conclusions: Lower urinary tract symptoms and abnormal uroflowmetry findings, which can lead to further progressive renal and urinary disorders, are common in DS children. Therefore, lower urinary tract functions should be assessed at the life‐long regular medical check‐ups for subjects with DS.